The Effects of Financial Performance toward Firm Value on Tourism, Hotel and Restaurant, and Transportation Sectors Listed on Indonesia Stock Exchange - Variyetmi Wira (Politeknik Negeri Bengkalis, 2021)
This study aims to examine the effect of financial ratios on firm value. The sample was chosen using purposive sampling with the data collection period 2016-2019, particularly in the tourism, hotels and restaurants, and transportation sectors listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, in order to obtain 45 companies per year. The data was collected through the datastream and www.idx.co.id website, and analyzed by employing SPSS 26 version. Financial performance variables are measured using Current ratio, Acid test ratio, Debt ratio, Debt to Equity ratio, Receivables collection period, Accounts receivable turnover, Gross Profit Margin and Net Profit Margin, while the firm value variable is measured by Price to Book Value (PBV). Since the data should meet the classical assumption test, therefore, normality test, multicollinearity test, heteroscedasticity and autocorrelation were carried out. The results showed that the debt ratio, accounts receivable turnover and net profit margin had a significant effect on firm value. On the other hands, other ratios such as current ratio, acid test ratio, debt to equity ratio, accounts receivable collection period, and gross profit margin do not have a significant effect on firm value.